On place-based artist pedagogies : Asiko Art School and the Nordic/Baltic Studio for Continued Engagement - (:unkn) unknown (Taideyliopiston Kuvataideakatemia, 2024)
This volume opens a path that teaches us about the material possibilities occurring beyond the given lenses of normative pedagogies and thinking in the arts. Let's give them shelter in our own bodies, through a careful reading, and let them teach us how to unlearn the hegemonic perceptual ecology. Give them the resonance to create other pedagogic ecologies.
Editor's note / Nana Ama Bentsi-Enchill -- Foreword / Luis Guerra Miranda -- Knowledge and to be Known / Aura Seikkula -- On the origins of Àsìkò: Curating at CCA Lagos / Bisi Silva -- On the Nordic/Baltic Studio: Seeking a space of exception (1 of 4) / Daniel Peltz -- I long for my body to walk with me / Tilda Dalunde -- Reminiscing Àsìkò / Odun Orimolade -- Memories transform like the textures of dreams / Meri Linna -- On the Nordic/Baltic Studio: Embedded installation (2 of 4) / Daniel Peltz -- Reflections on Trakthyggesbruk or the practice of cutting down a tree / David Larsson -- On the Nordic/Baltic Studio: Offerings (3 of 4) / Daniel Peltz -- A conversation on Disobedience (and) Matters / Tarcisio Almeida & Amilcar Packer -- Reflections on the Pedagogical Form and Curatorial Authority: On Bisi Silva and kąrî'kạchä seid'ou / Kwasi Ohene-Ayeh -- On the Nordic/Baltic Studio: The barely there institution (4 of 4) / Daniel Peltz -- A Conversation On Roving Pedagogies and Envisioning the future of Àsìkò / Oyindamola Faithful & Ama Ofeibea Tetteh.
Keywords: Art--Study and teaching.; Art--Research.; pedagogiikka; taidepedagogiikka; taideoppilaitokset; taidekorkeakoulut; tutkimus; yhteistyö